A Systematic Review and Meta-Analysis on the Association between Hypertension and Tinnitus. (31st December 2015) - Yang, Pan; Ma, Wenjun; Zheng, Yiqing; Yang, Haidi; Lin, Hualiang
Abstract : Hypertension has been suggested to be one possible risk factor of tinnitus, but the association between hypertension and tinnitus remains uncertain. The authors performed a meta-analysis of the existing studies on the association between hypertension and tinnitus. We performed literature search of studies using SinoMed, CNKI, WanFang, PubMed, Scopus, Web of Science, and Google Scholar. Studies reported the odds ratio and 95% confidence interval (CI) (or provided sufficient information for calculation) of the association between hypertension and tinnitus were included. A total of 19 eligible studies with 20 effect estimates were used in this study. They included 63, 154 participants with age ranging from 14 to 92. The pooled OR, which was pooled using a random effects model, was 1.37 (95% CI: 1.16 to 1.62). There was no evidence of publication bias (p = 0.11 for Begg's test, p = 0.96 for Egger's test). By meta-regression, we found that study design may be one possible factor of heterogeneity. Sensitivity analysis found that the result was stable. This study suggests that hypertension might be one risk factor of tinnitus, and hypertension prevention and control might be helpful in preventing tinnitus.